Development of Learning Media with Mathematical Understanding in Geometric Sequences and Series within Malay Islamic Context - Amaliah, Suci; Syutaridho; Ramury, Feli; Fitrianti, Yuli (Mathematics Education Journal, 2023)
This research aims to develop mathematical learning materials for understanding geometric sequences and series within the context of Malay Islamic culture, which can provide a valid and practical connection to mathematics and enhance mathematical comprehension skills. The research follows the Tessmer 1993 research procedure, encompassing two stages: introduction and prototyping, with a formative evaluation process. The research findings indicate that the learning materials are suitable for implementation, as demonstrated by assessments. The validity of the materials, as assessed by experts, is 93%, signifying their high suitability. The practicality of the learning materials, based on student feedback, is 79%, indicating their practical utility. As for their potential to enhance mathematical abilities, the results show an 82% positive impact on mathematical understanding abilities, as determined from student practice. Furthermore, the mathematical understanding ability of students using these learning materials was rated at 75%, indicating a high level of comprehension of geometric sequence and series content. Consequently, the developed learning materials are suitable for use in the educational process. DOI: https://doi.org/10.22342/jpm.17.3.21971.379-396